Charity as a Manifestation of Altruism in the Context of the Humanitarian Crisis in Ukraine - Гуменюк, Юлія Валентинівна (Київський національний університет імені Тараса Шевченка, 2025)
The article identifies the characteristic features and peculiarities of the humanitarian crisis in Ukraine. The author establishes that moral values and principles become extremely important in times of crisis, since the negative experience that a person goes through in a crisis period changes the personality and meaning of his or her life, and thus values. In times of upheaval, the issue of charity is particularly relevant and requires socio-philosophical reflection. The article studies the transformation of ideas about charity in the etymological context and analyses historical types of charity (ancient, Christian and modern). The author presents the Ukrainian traditions of charity, which date back to the times of Kyivan Rus and the Hetmanate, notes the Soviet era, when Ukrainian charity was forced to be suppressed, and the new wave of charity development in the times of Ukraine's proclaimed independence. The author proposes the newest historical type of charity, which should be associated with effective altruism. It is determined that this type of charity is a continuation of the modern type with new characteristic features of rationalisation of charitable activities, use of scientific achievements, intensive institutionalised, anonymous, professional philanthropy, which aims to solve not only individual and local social problems, but also global civilisation challenges. The author presents the legal regulation of charitable activities in Ukraine; analyses the processes of charity institutionalisation.

У статті визначені характерні ознаки та особливості гуманітарної кризи в Україні. Встановлено, що моральні цінності та принципи в період кризи стають надважливими, оскільки негативний досвід, який переживає людина в кризовий період, змінює особистість та сенс її життя, а отже й цінності. В період потрясінь питання благодійності є особливо актуальним і потребує соціально-філософського осмислення. Проведено дослідження трансформації уявлень про благодійність в етимологічному контексті та проаналізовано історичні типи благодійності (античний, християнський та новочасний). Представлено українські традиції благодійності, витоки яких сягають доби Київської Руси та Гетьманщини, відмічено радянську добу, коли благодійність українців була вимушено пригнічена, і нова хвиля розвитку доброчинності в часи проголошеної Незалежності України.Запропоновано новітній історичний тип благодійності, який слід пов’язувати з ефективним альтруїзмом. Визначено, що цей тип благодійності є продовженням новочасного типу з новими характерними ознаками раціоналізації благодійної діяльності, використання досягнень науки, інтенсивної інституціоналізованої, анонімної, професійної філантропії, яка має на меті вирішення не лише індивідуальних та локальних суспільних проблем, а й глобальних цивілізаційних викликів. Представлено правове регулювання благодійної діяльності в Україні; проаналізовано процеси інституціоналізації благодійності.
Благодійність як прояв альтруїзму в умовах гуманітарної кризи в Україні
Keywords: altruism; charity; humanitarian crisis; patronage; moral values; philanthropy; sponsorship; society; social sphere; альтруїзм; благодійність; гуманітарна криза; доброчинність; меценатство; моральні цінності; філантропія; спонсорство; суспільство; соціальна сфера